Higher education in emergencies : international case studies - Sengupta, Enakshi (Innovations in higher education teaching and learning ;, 2023)
Today's world is fraught with perils and pandemics. Education offers structure, stability, and hope for the future, supporting conflict resolution, peacebuilding efforts, and scientific research that can help prevent and mitigate both natural and manmade disasters. With these values in mind, how can universities apply their experiences from the COVID-19 pandemic to other emergency situations? How can they ensure accessibility to education under any circumstances without compromising on quality? With diverse contributions from Afghanistan, Turkey, Lebanon, Pakistan, Kenya, India, Saudi Arabia, and Bangladesh, Higher Education in Emergencies: International Case Studies challenges educators to design curriculums that focus on resilience and equip staff with the capability to navigate future scenarios, and students with the skills they need to someday solve them. Avoiding prescriptive standards and advocating for programmes that address the needs of individual campuses, chapters feature evidence-rich case studies that identify both the gaps in addressing vulnerabilities as well as exemplary responses that have led the way in promoting institutional adaptability. Championing a variety of the lessons taken from across the globe, Higher Education in Emergencies: International Case Studies provides a critical toolkit for preparing universities for the next pandemic, earthquake, or civil conflict.